Work From Home and the Office Real Estate Apocalypse - Gupta, Arpit,Mittal, Vrinda,Nieuwerburgh, Stijn van (National Bureau of Economic Research, 2022)
We study the impact of remote work on the commercial office sector. We document large shifts in lease revenues, office occupancy, lease renewal rates, lease durations, and market rents as firms shifted to remote work in the wake of the Covid-19 pandemic. We show that the pandemic has had large effects on both current and expected future cash flows for office buildings. Remote work also changes the risk premium on office real estate. We revalue the stock of New York City commercial office buildings taking into account pandemic-induced cash flow and discount rate effects. We find a 45% decline in office values in 2020 and 39% in the longer-run, the latter representing a 453 billion value destruction. Higher quality office buildings were somewhat buffered against these trends due to a flight to quality, while lower quality office buildings see much more dramatic swings. These valuation changes have repercussions for local public finances and financial sector stability
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Gewerbeimmobilien; Immobilienmarkt; Telearbeit; Coronavirus; New York; USA; Financial Forecasting and Simulation; General; Nonagricultural and Nonresidential Real Estate Markets